Design and Implementation of Solar-Powered Submersible Water Pump for Irrigation System in Subak Munduk Babakan Sangeh, Bali - Ida Bagus Irawan PURNAMA; Ketut Vini ELFAROSA; Ida Bagus Ketut SUGIRIANTA; Anak Agung Putri INDRAYANTI; Made WIDIANTARA (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2024)
This paper presents a comprehensive study on the design, implementation, and performance evaluation of a Solar-Powered Submersible Water Pump (SPSWP) system tailored for agricultural irrigation in Subak Munduk Babakan, Sangeh, Bali. With a focus on sustainable agriculture and water resource management, the system addresses the challenges of water scarcity during the dry season in the absence of natural irrigation sources. The SPSWP system, consisting of solar panels with a pump controller, a submersible pump, and a water tank, harnesses solar energy to power the pump, eliminating the need for extensive infrastructure. The research encompasses site survey and mapping, analysis and design, installation, benefits beyond irrigation, and technical measurements. The implementation shows promising results in overcoming water scarcity issues. The system's advantages include minimal maintenance, cost savings, and enhanced reliability. Additionally, the SPSWP system serves as an educational site for renewable energy study and awareness. Performance metrics are measured and discussed, including solar irradiance, voltage, current, solar panel temperature, and water discharge. The results indicate fluctuating solar energy availability, with voltage and current aligning with solar panel specifications. The system demonstrates a water discharge rate of 0.56 liters/second, showcasing promising outcomes in addressing water scarcity challenges for agricultural irrigation. Further research and monitoring are required to assess the long-term performance and sustainability of the system.